A novel approach of user existence awareness using adaptive spectrum sensing controllers in emergency‐based cognitive radio adhoc networks. (20th May 2018) - Sudhakaran, Chitra; Suganthi, M.
Summary: Spectrum sharing can be considered as an alternative solution to overcome spectrum limitation. Cognitive radio is the most important spectrum sharing technique in wireless communication system, which aims to enhance the utilization of radio frequency spectrum. Identification of spectrum environments like location of both licensed and unlicensed users has been considered in cognitive radio technology. In this paper, cognitive controller is an emergency repairing unit, which is introduced to maximize the number of connected users in an emergency situation. The analysis shows that the sensing efficiency of fixed sensing controller to identify users is limited to its sensing region. A hybrid technique with overlay and underlay accessing to perform data offloading in emergency situations and to connect the disconnected users is proposed to enhance the location sensing efficiency of the controller. A cognitive user node located at the interference region of controller experiences hidden node problem and causes interference to other users. In order to identify such users, an adaptive and cooperative sensing‐based controller is proposed, and efficiency of which is compared with the efficiency of fixed sensing controller. Theoretical and simulation analysis explores that the sensing capacity of adaptive sensing controller provides 42% of higher efficiency than the fixed sensing method. Abstract : Main objective of the proposed work is to connect maximum number of emergency users as the trapped lives during the disasters such as earthquakes, and floods need a communication system with the same priority as they need food water, medical facility and shelter. This paper addresses an approach by introducing controllers equipped in vehicles, which has cognitive capability to emergency support systems and thus providing a support to broaden the obtained bandwidth with the help of data offloading process in licensed band.